Reactivity in cell culture medium and in vitro anticancer activity of 3,5-di-tert-butylcatechol: link to metal-catechol interactions - Aviva Levina; Debbie C. Crans; Peter A. Lay (Frontiers in Chemical Biology)
IntroductionCatechol moieties are common in natural bioactive molecules, and their ability to bind metal ions is widely explored both naturally with siderophores and in the development of metal-based drugs. The reactivities and biology activities of a sterically hindered model catechol compound, 3,5-di-tert-butylcatechol (dtbH2) and its oxidation product 3,5-di-tert-butyl-o-quinone (dtbQ), were studied in cell culture medium to understand better the medicinal roles of this class of molecules.MethodsAnti-proliferative activities of dtbH2 and dtbQ in fresh and aged solutions of the molecules were studied in two common human cancer cell lines, T98G (glioblastoma) and A549 (lung carcinoma). Electrospray mass spectrometry and UV/Vis spectroscopy were used to study the reactivities of the molecules in buffer solutions and cell culture medium, in the presence and absence of glutathione and imidazole.Results and DiscussionThe dtbH2 and dtbQ molecules showed high anti-proliferative activity (IC50 < 10 μM in 72 h assays) in T98G and A549 cell lines in the absence of added metal ions. The activity was observed when dtbH2 and dtbQ were freshly added to cell culture medium, while pre-incubation with the medium for 24 h reduced their activity 5-10-fold. This deactivation was avoided when the biological reductant, glutathione (GSH), was added to the medium at a physiologically relevant intracellular concentration (5.0 mM). These results were explained by speciation studies (UV/Vis spectroscopy and mass spectrometry) of dtbH2 and dtbQ in cell culture medium, aqueous buffers, or organic solvents in the presence or absence of GSH. These studies showed that a redox equilibrium was established between dtbH2 and dtbQ, with the latter rapidly coupling the GSH in an oxidative manner. The resultant adduct is likely to be responsible for the high toxicity of dtbH2 and dtbQ in GSH-rich cancer cells via oxygen-dependent radical chain reactions. Deactivation of dtbH2 and dtbQ in cell culture medium in the absence of GSH was due to the reactions of dtbQ with nucleophiles, such as amino acids, followed by the formation of polymeric species. The reported high anti-proliferative activity of V(V)-catecholato complexes can be explained by a combination of their efficient cellular uptake and rapid decomposition in thiol-rich intracellular environment with the formation of active V(V) and dtbH2/dtbQ adducts with thiols (mainly GSH). Slower decomposition and deactivation of the complexes was observed in thiol-poor extracellular environments. These data show that speciation in cell culture medium is crucial for the biological activity not only of metal complexes but also of their ligands when the complexes dissociates.